Correlation between the Results of Sequential Extraction and Effectiveness of Immobilization Treatment of Lead- and Cadmium-Contaminated Sediment - Milena B. Dalmacija; Miljana D. J. Prica; Bozo D. Dalmacija; Srdjan D. Roncevic; Ljiljana M. Rajic (The Scientific World Journal)
The assessment of the quality of sediment from the Great Backi Canal (Serbia), based on the pseudo-total lead (Pb) and cadmium (Cd) content according to the corresponding Dutch standards and Canadian guidelines, showed its severe contamination with these two metals. A microwave-assisted BCR (Community Bureau of Reference of the Commission of the European Union) sequential extraction procedure was employed to assess their potential mobility and risk to the aquatic environment. Comparison of the results of sequential extraction and different criteria for sediment quality assessment has led to somewhat contradictory conclusions. Namely, while the results of sequential extraction showed that Cd comes under the high-risk category, Pb shows low risk to the environment, despite its high pseudo-total content. The contaminated sediment, irrespective of the different speciation of Pb and Cd, was subjected to the same immobilization, stabilization/solidification (S/S) treatments using kaolinite, montmorillonite, kaolinite-quicklime, montmorillonite-quicklime, fly ash, zeolite, or zeolite-fly ash combination. Semi-dynamic leaching tests were conducted for Pb- and Cd-contaminated sediment in order to assess the long-term leaching behavior of these metals. In order to simulate “worst case” leaching conditions, the semi-dynamic leaching test was modified using 0.014 M acetic acid (pH = 3.25) and humic acid solutions (20 mg TOC l-1) as leachants instead of deionized water. The effectiveness of S/S treatment was evaluated by determining diffusion coefficients (De) and leachability indices (LX). The standard toxicity characteristic leaching procedure (TCLP) was applied to evaluate the extraction potential of Pb and Cd. A diffusion-based model was used to elucidate the controlling leaching mechanisms. Generally, the test results indicated that all applied S/S treatments were effective in immobilizing Pb and Cd, and the treated sediments may be considered acceptable for “controlled utilization” based on LX values, irrespective of their different availability in the untreated samples. In the majority of samples, the controlling leaching mechanism appeared to be diffusion, which indicates that a slow leaching of Cd and Pb could be expected when the above S/S agents were applied. The TCLP results showed that all S/S samples were nonhazardous.